El falso juramento y sus consecuencias sociorreligiosas en las inscripiciones de confesión lidiofrigias - Lozano, Arminda (ARYS. Antigüedad: Religiones y Sociedades, 2020)
The proposed study analyses one of the “sins” that appears more often in the inscriptions related to confessions and expirations of the lidio-phrygich minorasiatic area, which is the false oath, that is, a false affirmation made before a divinity. The reasons for this perjury are varied and this study will analyze those more commonly used in the texts by way of relevant and outstanding examples. This method will also serve to demonstrate the procedures followed by the victims of such perjuries in order to receive the applicable punishments by the divinity, as well as the typology, those people affected by, etc. This analysis will allow gaining insight into the religious perceptions in rural areas of Minor Asia and the prominent role played by the gods, that is, the temples and priesthood in these communities.